Performance of Three Microimmunofluorescence Assays for Detection of Chlamydia pneumoniae Immunoglobulin M, G, and A Antibodies - Bennedsen, Mette (American Society for Microbiology, 2002)
The microimmunofluorescence (MIF) test is considered the “gold standard” for laboratory diagnosis of acute and chronic Chlamydia pneumoniae infection. The performance of a MIF test based on C. pneumoniae antigen from Washington Research Foundation (WRF) was compared with those of assays from Labsystems (LAB) and MRL Diagnostics (MRL) by investigation of sera from three groups of patients: group I, 83 sera from 28 patients with atypical pneumonia; group II, 37 sera from 16 patients with acute C. pneumoniae or Chlamydia psittaci respiratory tract infection confirmed by PCR or culture; group III, 100 sera from 100 persons enrolled in the Copenhagen City Heart Study. The accordance among the results of the WRF assay and the two commercial assays was excellent for the immunoglobulin M (IgM) antibody detection rate (98%). The accordance in detection rates for IgG and IgA antibodies in sera from patients with acute infections was acceptable (87 and 88%), and in sera from group III, it was excellent (95 and 97%). The determinations of endpoint titers were reproducible with <1 dilution step difference for all three methods, except that the mean IgM antibody titer found by the LAB assay was almost 2 dilution steps higher than that found by the other two methods. Although the three assays use different C. pneumoniae strains as antigens, the detection rates and IgG and IgA endpoint titers were similar. The difference in endpoint titers of IgM antibodies is of no major concern, as the diagnosis of acute C. pneumoniae infection rests on the presence of IgM antibodies, not on their level.